PENGENALAN CLOUD COMPUTING DAN IOT PADA SMKN 6 KOTA TANGERANG SELATAN - Fikri Hidayatullah; M. Dimas Ramdani F. S.; Adji M. Pramudita; Caesar Ariel R.; Akmal Indrayansyah; Santi Ayu P.; Vera Oktaviani; Nuraina; Saiyah Awaliyah; Jilan Fahri Zaenudin; Juri Pebrianto (Shofanah Media Berkah, 2025)
Pengabdian Kepada Masyarakat (PKM) bertema